2007
DOI: 10.1016/j.ydbio.2006.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Notch and Numb are required for normal migration of peripheral glia in Drosophila

Abstract: A prominent feature of glial cells is their ability to migrate along axons to finally wrap and insulate them. In the embryonic Drosophila PNS, most glial cells are born in the CNS and have to migrate to reach their final destinations. To understand how migration of the peripheral glia is regulated, we have conducted a genetic screen looking for mutants that disrupt the normal glial pattern. Here we present an analysis of two of these mutants: Notch and numb. Complete loss of Notch function leads to an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 62 publications
2
48
0
Order By: Relevance
“…In Drosophila, the wrapping glial cells originate from progenitor cells of the CNS, and as soon as they are specified, they start to migrate out into the periphery, in part using the same molecular machinery that also directs the navigation of axonal growth cones (Edenfeld et al, 2007;von Hilchen et al, 2008von Hilchen et al, , 2010Sepp and Auld, 2003a;Silies and Klämbt, 2010). At the beginning of larval life, the wrapping glial cells start to grow and extend enormous processes, reaching more than 1 mm in length.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, the wrapping glial cells originate from progenitor cells of the CNS, and as soon as they are specified, they start to migrate out into the periphery, in part using the same molecular machinery that also directs the navigation of axonal growth cones (Edenfeld et al, 2007;von Hilchen et al, 2008von Hilchen et al, , 2010Sepp and Auld, 2003a;Silies and Klämbt, 2010). At the beginning of larval life, the wrapping glial cells start to grow and extend enormous processes, reaching more than 1 mm in length.…”
Section: Discussionmentioning
confidence: 99%
“…To follow Nrx-IV exon3 independently from Nrx-IV exon4 we generated constructs that carry a Myc tag just C-terminal to the cleavage site of the signal peptide. We had previously shown that Neurexin IV tolerates the inclusion of a GFP moiety (Edenfeld et al, 2007) and thus expected that the inclusion of a Myc tag at the same site would not change binding behavior. To further control for minor effects, we generated both a Nrx-IV exon3-myc and a Nrx-IV exon4-myc protein.…”
Section: Wrapper Prefers Interaction With Neurexin IV Exon4 Compared mentioning
confidence: 99%
“…In principle, cells can either migrate individually or can move as chains or groups of cells through the body. Peripheral glial cells derived from the neural crest move as a continuous group of cells and similarly glial cells were reported to migrate in chains in the Drosophila PNS (Gilmour et al, 2002;Aigouy et al, 2004;Lyons et al, 2005;Edenfeld et al, 2007). Likewise in the CNS, glial cells often migrate toward their final destination and on their way can be guided by the same signaling systems that are used by the navigating neuronal growth cones (Kinrade et al, 2001;Tsai and Miller, 2002;Jarjour and Kennedy, 2004).…”
Section: Introductionmentioning
confidence: 99%